Tiller removal does not increase maize grain yield, regardless of the sowing dat A remoção dos perfilhos não aumenta o rendimento de grãos do milho, independentemente da época de semeadura - Schmitt A.* (2012)
Historically, tillers have been considered detrimental to maize because they do not produce ears and may act as sinks competing for carbohydrates with the main stem. This work was carried out aiming to evaluate the effect of tiller removal on maize grain yield at different sowing dates. The experiment was set during the 2006/07 and 2008/09 growing seasons. A randomized complete block design disposed in split-plots was used. Two sowing dates were tested in the main plots: second half of October (recommended) and second half of December (late). Four tiller's fates were evaluated in the split-plots: tiller removal when the main stem had six expanded leaves (V6), nine expanded leaves (V9), fifteen expanded leaves (V15) and tiller maintenance until harvesting. Hybrid P30F53 was sowed at 55,000 plants ha-1, with a row spacing of 0.7m. The percentage of plants with tillers and the number of tillers per plant were higher when maize was sown in October than in December. There was no grain yield difference between treatments where tillers were preserved and those where they were removed at V6, V9 or V15, regardless of sowing date. Such behavior demonstrates that tillers are not sinks that compromise maize agronomic performance. Furthermore, tillers may contribute positively to grain yield when maize is sown in October.